PERAN GURU PPKn SEBAGAI EVALUATOR DALAM MENINGKATKAN HASIL BELAJAR SISWA - Amilina Laia (Universitas Nias Raya, 2023)
This research aims to determine the role of PPKn teachers as evaluators in improving the learning outcomes of Class X students at SMA Negeri 1 Amandraya for the 2022/2023 academic year. This type of research is descriptive type qualitative research. This research was carried out from June 2 to June 30 2023. Based on the results of the research and discussion that have been obtained, it can be concluded that the role of the teacher as an evaluator of student learning outcomes is that: (1) Subject teachers, especially Civic Education subjects, always carry out evaluations to improve student learning outcomes from three domains, namely affective, psychomotor and affective. and teachers carry out evaluation planning carefully based on the evaluation objectives that have been previously determined, (2) The form of evaluation carried out is by providing several techniques such as test techniques, non-test techniques, observation or observation. With the evaluation, it can be ensured that the output the learning process will be according to plan. This can be seen from the increase in student learning outcomes after taking the final semester exams both in terms of cognitive, affective and psychomotor aspects. The researcher's advice is for teachers at SMA Negeri 1 Amandraya, that their current performance is very good and that in the future it will be even better.